A Study of the Impact of Spirituality and Curiosity on Life Satisfaction in Chinese Christian Teachers. Issue 3 (2nd September 2022) - Lam, Chi-Yeung
Abstract: Previous research demonstrated that both spirituality and curiosity were positively associated with life satisfaction. However, limited research investigated the relationship between spirituality and curiosity. One hundred eight Chinese Christian teachers participated in an online questionnaire that measured their spirituality, curiosity, and life satisfaction. Results showed that three dimensions of curiosity, namely, joyous exploration, deprivation sensitivity, and stress tolerance, were significantly associated with spirituality. Deprivation sensitivity was found to be a significant competitive mediator (suppressor) of the relation between spirituality and life satisfaction, indicating the anxiety embedded in deprivation sensitivity might interfere with Christian teachers' life satisfaction. The finding provides support for the importance of fostering psychological capital and developmental assets for Christian teachers' positive development.